Studi Komparatif Pemikiran Al-Farmawi, Baqir Shadr dan Abdussatar Fathallah tentang Tafsir Maudhui - Badruzzaman M. Yunus; Abdul Rohman; Ahmad Jalaludin Rumi Durachman (UIN Sunan Gunung Djati Bandung, 2021)
This article discusses the interpretation of maudhui' in the perspective of experts, namely Abdul Hayy Al-Farmawi, Muhammad Baqir Ash-Sadr, and Abdussatar Fathullah Said. The purpose of this paper is to find out how the views of each of the three figures regarding the interpretation of maudhui and the extent to which the similarities and differences. In writing this research, the method that will be used is a qualitative method based on library research and comes from the thoughts of three main characters, namely Abdul Hayy Al-Farmawi with his book Al-Bidâyah Fî Tafsîr Al-Maudhû'i; Muhammad Baqir Sadr with his book Al-Madrasah Al-Qurâniyyah; and Abdussatar Fathullah Saíd with his book Al-Madkhal Ilâ At-Tafsîr Al-Maudhûí. The results obtained are that the three figures have the same views regarding the urgency of this maudhûî' interpretation method; they state that this method can answer contemporary problems and can get the meanings of the Qur'an comprehensively. The difference lies only in the initial starting point for the operation of the process and the fundamental steps it formulates.